Nutrition knowledge of people with eating disorders - Beata Całyniuk; Michał Górski; Jagoda Garbicz; Elżbieta Grochowska-Niedworok (National Institute of Public Health - National Institute of Hygiene, 2019)
Background: Eating disorders are an increasingly common health problem that is a major therapeutic challenge. For many years, the basic form of therapy used to be psychiatric and psychotherapeutic treatment, but now it is postulated that the dietetician should also be part of the therapeutic teams. Objective: The main purpose of the study is to assess nutrition knowledge of people with eating disorders with consideration to their age, place of living, education, BMI, type of disease, participation in dietary consultations and in therapy. Material and methods: Nutrition knowledge of the respondents was assessed by means of an author's survey questionnaire. The questionnaire was published in one of the social portals in the "Eating disorders - tackling" group gathering people with different types of eating disorders. The survey questionnaire consisted in 33 questions. Arithmetic mean and standard deviation for the number of correct answers provided by the respondents by the selected criteria. Results: In terms of age, the least nutrition knowledge was attributable to the persons below 20 years of age (25.24 points in average). When considering the place of living, the least nutrition knowledge was revealed among the subjects living in medium cities (between 20 and 100 thousand of population) i.e. 25.31 points. In terms of education, the least nutrition knowledge was recorded in people with vocational education (24.83 points). When classifying the respondents by BMI, the highest average score was gained by the respondents with normal body mass index (BMI) (26.42 points). Conclusions: The study on the level of nutrition knowledge among the people with eating disorders demonstrated that this knowledge was selective and insufficient to provide rational nutrition. It aimed at teaching the rules of healthy lifestyle and nutrition and thorough discussing of all nutrients, their functions and effect on the body.